2013
DOI: 10.1016/j.mod.2012.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Primary cilia and forebrain development

Abstract: With a microtubule-based axoneme supporting its plasma membrane-ensheathed projection from the basal body of almost all cell types in the human body, and present in only one copy per cell, the primary cilium can be considered an organelle sui generis. Although it was first observed and recorded in histological studies from the late 19th century, the tiny structure was essentially forgotten for many decades. In the past ten years, however, scientists have turned their eyes once again upon primary cilia and real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 53 publications
2
20
1
4
Order By: Relevance
“…During embryonic development, this sensory organelle was found to be required for survival and patterning of the mouse embryo (Nonaka et al 1998; Huangfu and Anderson 2005). More recently, this organelle was also implicated in determination, differentiation and maturation of a wide variety of organs within the body, including the central nervous system, skeleton, heart and blood vessels, kidney, and liver (Tasouri and Tucker 2011; Willaredt et al 2013). During formation of these organs, primary cilia function as sensory organelles, playing a pivotal role in integrating signals derived from a number of signalling transduction pathways, such as hedgehog, wingless, fibroblast growth factor, platelet-derived growth factor, and planar cell polarity (Goetz and Anderson 2010).…”
Section: Introductionmentioning
confidence: 99%
“…During embryonic development, this sensory organelle was found to be required for survival and patterning of the mouse embryo (Nonaka et al 1998; Huangfu and Anderson 2005). More recently, this organelle was also implicated in determination, differentiation and maturation of a wide variety of organs within the body, including the central nervous system, skeleton, heart and blood vessels, kidney, and liver (Tasouri and Tucker 2011; Willaredt et al 2013). During formation of these organs, primary cilia function as sensory organelles, playing a pivotal role in integrating signals derived from a number of signalling transduction pathways, such as hedgehog, wingless, fibroblast growth factor, platelet-derived growth factor, and planar cell polarity (Goetz and Anderson 2010).…”
Section: Introductionmentioning
confidence: 99%
“…11 In different areas of the brain, such as the cortex, hippocampus and cerebellum, it has been clearly demonstrated that primary cilia disruption severely affects cell cycle progression in neuronal progenitors, and that this effect is at least in great part due to impaired Shh signaling, mostly evidenced in Gli3 misprocessing. 28,29 Finally, and as discussed below, Hh is not the only signaling pathway acting through primary cilia. For example, as recently reported, signaling through an orphan cilia-localized G-Protein Coupled Receptor (GPCR) favor cell cycle exit and differentiation of radial glia progenitors, through binding to a cerebrospinal fluid factor up-regulated in the neurogenic phase (Fig.…”
Section: Cilia and The Cell Proliferation/neurogenesis Balancementioning
confidence: 95%
“…La dégénérescence des photorécepteurs de la rétine est très fréquente dans les ciliopathies. Le cil pourrait aussi être en cause dans les ataxies spinocérébelleuses [26,62], la chorée de Huntington, la maladie de Parkinson, ou encore certains syndromes neurologiques tels que la schizophrénie ou la dyslexie [2,5]. Les recherches futures, notamment l'exploitation d'animaux chez lesquels un knock-out conditionnel permettrait de cibler l'invalidation des gènes ciliaires dans le cerveau adulte, devraient offrir un nouvel éclairage sur ces questions.…”
Section: Cils Migrations Neuronales Et Projections Axonalesunclassified
“…Mais, à l'époque, les cils étaient considérés comme des organites vestigiaux sans fonction particulière [1][2][3]. Ce n'est qu'avec l'analyse des lignées de souris dépourvues de cil et la description des syndromes humains dus à des dysfonctionnements ciliaires, que les fonctions de ce petit organite solitaire se sont révélées essentielles à de nombreux processus développementaux et, notamment, à la morphogenèse cérébrale [4,5]. Les ciliopathies sont des maladies génétiques dues à des dysfonctionnements du cil d'origine variable [6,67] ( §).…”
unclassified